2023
DOI: 10.3390/wind3010003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ice Formation on Vertical Axis Wind Turbine Performance and Aerodynamics

Abstract: This study investigated the impact of ice formation on the performance and aerodynamics of a vertical axis wind turbine (VAWT). This is an area that is becoming more prevalent as VAWTs are installed alongside horizontal axis wind turbines (HAWTs) in high altitude areas with cold and wet climates where ice is likely to form. Computational fluid dynamics (CFD) simulations were performed on a VAWT without icing in Ansys to understand its performance before introducing ice shapes obtained through the LewInt ice ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Sean et al investigated the effects of glaze ice and freezing ice conditions on wind turbine aerodynamics through numerical simulations. It was found that more ice is formed at lower temperatures in freezing ice conditions, and the wind turbine performance was reduced by a maximum of 40% [27]. Mustafa et al investigated the static performance of a wind turbine at different uniform wind speeds between cut-in and cut-out wind speeds by simulating and analyzing a 5 MW wind turbine blade with light icing.…”
Section: Introductionmentioning
confidence: 99%
“…Sean et al investigated the effects of glaze ice and freezing ice conditions on wind turbine aerodynamics through numerical simulations. It was found that more ice is formed at lower temperatures in freezing ice conditions, and the wind turbine performance was reduced by a maximum of 40% [27]. Mustafa et al investigated the static performance of a wind turbine at different uniform wind speeds between cut-in and cut-out wind speeds by simulating and analyzing a 5 MW wind turbine blade with light icing.…”
Section: Introductionmentioning
confidence: 99%